MODIFIKASI DIAMETER INLET DAN PENGARUH KEKERASAN KARET TERHADAP HASIL LADA PADA MESIN PENGUPAS LADA SISTEM CRUSHER - Firlya Rosa; Rodiawan Rodiawan; elyas kustiawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2018)
Based on previous research, specifications of machine have a slope of a dish of 0.68 ° and inlet diameter of 30 mm, produce 1 kg/hour of input capacity and 0.64 kg/hour of output capacity. From the evaluation results, to increase the input capacity it is necessary to increase the inlet diameter and analyze the effect of rubber hardness on the results of peeling pepper. Modifiying the inlet diameter, input capacity increase to 6 kg/hour or increasing 5 times compared to the input capacity of the previous research. For hardness of rubber 60 shore A, the percentage of pepper peeled was 72.13% with an engine output capacity of 4.33 kg/hour. For rubber hardness of 70 shore A, the percentage of pepper peeled was 73.03% with an engine output capacity of 4.38 kg / hour. Visually, dry pepper with a hardness of 60 shore A whiter than dry pepper hard with a hardness of 70 shore A.